Improving Color Recognition Ability Though Painting in Group B of TK One Roof Bulubete - Nur Andriani; Arsyad Said; Syamsidar Syamsidar (Universitas Muhammadiyah Palu, 2021)
The research problem is children's ability to recognize color has not developed as expected. This aims to improve children's ability to recognize colors through painting. Subjects and research setting are 20 children of group B at TK Satu at Bulubete, consisting of 10 boys and ten girls registered in the 2019/2020 school year. This research uses Kemmis and Mc. Taggart design was carried out in cycles. The data collection technique is observation, assignment, and documentation, then analyzed descriptively. In pre-action data, the ability to mention color, BSH category is 10%, MB 15%, and BB 75%. The ability to show color, BSH category 10%, MB 20%, and BB 70%. The ability to group colors, category BSB 5%, BSH 15%, MB 15%, and BB 65%. After using the painting method, the child's ability to recognize color has increased from cycle I to cycle II. The BSB, BSH, and MB categories' ability to name color from 60% to 85% (25%). The ability to show the BSB, BSH, and MB categories colors from 55% to 85% (30%). The BSB, BSH, and MB categories' ability to group colors from 65% to 85% (20%). There is an increase in children's ability to recognize color from cycle I to cycle II with an average of 25% in the BSB, BSH, and MB categories and 15% of children in the BB category. The results of this research prove that the painting method can improve children's ability to recognize color in group B TK Satu Atap Bulubete.